Marca como canal de transmissão de valores simbólicos - Oliveira, Estela Maris de Medeiros e (2018)
The visual signature of companies, products and services underwent transformations, from its emergence in antiquity to the present day. The brand is a strong channel of communication of intangible values that drives the symbolic exchanges of the consumer society of nowadays. In order to gather the theoretical foundations about the subject matter, this article presents a study that brings together definitions that support the aspirational role of brands in ontemporary society. It is discussed the divergence of terms used by authors of the area and the definitions in the design and marketing literature. As also, it is discussed which are their constituent elements related to image and identity, and how the semiotics of the brand and its signs works on practice.